The role of green open spaces in the mental health and happiness of urban communities - Tanwir, Siti Saroh; Huda, Ahmad Syaiful; Latif, Abdul; Syafi’i, Ahmad (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Mental health is the most important thing in human life, but in reality in Indonesia the level of mental health disorders is still high. People who live in urban areas are vulnerable to mental health disorders such as anxiety, stress and depression which are caused, among other things, by high work pressure and lack of recreational activities. Method: This article uses a non-experimental correlational method, collecting secondary data from various sources and journal articles without experimental manipulation. The focus is on urban communities. Findings: Difficulty accessing natural things, such as rural environments, even something